Analysis of the Effects of the Covid-19 Process on the Financial Performance of Businesses in the Defense Industry By the TOPSIS, EDAS, CoCoSo Method: ISE Sample - Aktepe, Cemalettin; İzgi, Fatma (InTraders International Trade Academic Journal, 2024)
The defense industry has recently received attention due to its significant advancements. This study examines the impact of the COVID-19 pandemic on the financial performance of companies operating in the Turkish defense sector. The financial data from 2019 to 2023 of defense industry firms listed on Borsa Istanbul, namely ASELS, OTKAR, PAPIL, SDTTR, NETAŞ, and KATMER, were analyzed. The primary objective of this research is to evaluate the financial performance of these companies during the pandemic by comparing it with the pre-pandemic period. In this context, eight financial ratios related to liquidity, turnover, financial structure, and profitability were utilized to assess financial performance. The criteria weights were determined using the Entropy method, and the performance rankings of the companies were established through Multi-Criteria Decision Making (MCDM) techniques, including TOPSIS, EDAS, and CoCoSo. This study offers a novel perspective by examining the effects of the COVID-19 pandemic on Turkish defense industry firms and uncovering their financial performance in comparison to previous periods. According to the results of the entropy method, the most significant criteria for evaluating the financial performance of companies listed on Borsa Istanbul (BİST) are Active Profitability Ratio (APR) and Equity Profitability Ratio (EPR). In the year 2020, which was significantly impacted by the pandemic, companies with strong financial performance included ASELS, PAPIL, SDTTR, and NETAŞ. Conversely, KATMER was identified as one of the companies with weaker financial performance during the same period.